Representasi Komunikasi Keluarga dalam Serial ‘Saiyo Sakato’: Analisis Semiotika Charles Sanders Peirce: Penelitian - Frelians, Pricilla Pascadeany; Seli, Sesilia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
As a form of mass communication, film functions not only as entertainment but also as a representation of social realities that shape public perspectives. This study analyzes the representation of family communication in the Saiyo Sakato serial using Charles Sanders Peirce’s semiotic approach. The research focuses on how meanings of family communication are constructed through visual signs, dialogue, and interactions within Minangkabau culture, which is matrilineal yet influenced by patriarchal values. A qualitative method was applied by examining all episodes of the serial based on the categories of icons, indexes, and symbols. The findings reveal that Saiyo Sakato portrays family communication as a process shaped by cultural values, emotional closeness, social hierarchy, and power dynamics within the family. These results highlight the role of media in shaping meanings related to family relationships in specific cultural contexts.